2016
DOI: 10.1016/j.envpol.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, accumulation and metabolization of the antidepressant fluoxetine by Mytilus galloprovincialis

Abstract: a b s t r a c tFluoxetine, a selective serotonin re-uptake inhibitor (SSRI) antidepressant, is among the most prescribed pharmaceutical active substances worldwide. This study aimed to assess its accumulation and metabolization in the mussel Mytillus galloprovincialis, considered an excellent sentinel species for traditional and emerging pollutants. Mussels were collected from Ria Formosa Lagoon, Portugal, and exposed to a nominal concentration of fluoxetine (75 ng L À1 ) for 15 days. Approximately 1 g of whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Interestingly, although their trajectories drastically varied, the mixture and fluoxetine treatments clustered near one another in multivariate space post‐depuration (Figure C, E), possibly because of the probable presence of norfluoxetine, fluoxetine's main biotransformation product. In mussels ( M. galloprovincialis ) exposed to fluoxetine norfluoxetine concentrations exceeded those of fluoxetine after 15 d of exposure (Silva et al ), and norfluoxetine was more prone to bioaccumulate than fluoxetine, although eliciting a similar biological effect (Daughton and Brooks ). Although it is possible that given more time the oysters would be able to recover completely from these exposures in a laboratory setting, it is currently unknown how accurate this prediction would be in the environment, where contaminants are introduced sporadically and for indeterminate durations (Rozman and Doull ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, although their trajectories drastically varied, the mixture and fluoxetine treatments clustered near one another in multivariate space post‐depuration (Figure C, E), possibly because of the probable presence of norfluoxetine, fluoxetine's main biotransformation product. In mussels ( M. galloprovincialis ) exposed to fluoxetine norfluoxetine concentrations exceeded those of fluoxetine after 15 d of exposure (Silva et al ), and norfluoxetine was more prone to bioaccumulate than fluoxetine, although eliciting a similar biological effect (Daughton and Brooks ). Although it is possible that given more time the oysters would be able to recover completely from these exposures in a laboratory setting, it is currently unknown how accurate this prediction would be in the environment, where contaminants are introduced sporadically and for indeterminate durations (Rozman and Doull ).…”
Section: Resultsmentioning
confidence: 99%
“…Chu et al [46] found increased concentrations of norfluoxetine in fish incubated with fluoxetine. The mussel M. galloprovincialis was exposed to a nominal concentration of fluoxetine (75 ng/L) for 15 days [47]. The authors observed that the concentration of fluoxetine and norfluoxetine increased from 2.53 and 3.06 ng/g dry weight after 3 days up to 9.31 and 11.65 ng/g after 15 days, respectively.…”
Section: Biotransformationmentioning
confidence: 99%
“…In addition, mussels filter large volumes of water and they are known as “suspension feeders”. They filter suspended materials and colloids and they are then known to efficiently bioaccumulate toxic compounds [ 23 , 24 ]. This species is therefore often used as a sentinel organism for the monitoring of coastal water pollution (mussel watch programs) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%